Wygląd Zenobii w Historia Augusta : asocjacje i inspiracje - Domazet, Radosław (Instytut Historyczny Uniwersytetu Wrocławskiego, 2024)
This paper analyses the description of Zenobia’s appearance in the Historia Augusta (HA Tyr. Trig. 15.8, 30.15). Descriptions of what the rulers mentioned in Historia Augusta looked like have yet to be comprehensively researched. Most articles focus on general remarks about their authorship and the similarities to the work of Suetonius, with no attempt being made to analyse specific descriptions as a separate topic. Thus, individual features of Zenobia’s physiognomy have so far not been discussed in published literature concerning the Palmyrene queen. Her appearance is in several respects identical to that of Diadumenian (HA Dd. 3.2–3), which tells us a lot about the creationof the passages by the editor of the Historia Augusta. Moreover, what has not been noticed in the literature beforeis that Zenobia's appearance resembles that of Giddenis, a woman from one of Plautus' comedies (Pl. Poen. 1112–1113). Therefore, this article is not only important with regards to research concerning the female body in antiquity, but it also draws attention to the previously unexplored influence of Plautus on the Historia Augusta
Keywords: Zenobia; Diadumenian; body; appearance; Historia Augusta; Plautus